Split-ring resonator with interdigital Split electrodes as detector for liquid and ion chromatography - Kirsten J. Dehning; Moritz Hitzemann; Stefan Zimmermann (Sensing and Bio-Sensing Research, 2024)
The analysis of food and drugs as well as the monitoring of chemical processes and bioreactors by high-performance liquid chromatography and ion chromatography requires universal, cost-effective, and sensitive detectors. Therefore, this work presents a split-ring resonator that detects changes in the electrical and dielectric properties of the eluate from liquid chromatography or ion chromatography by monitoring the amplitude of the transmitted signal using an envelope detector. The used split-ring resonator consists of a simple printed circuit board featuring two microstrip lines. One is formed to a ring with interdigital split electrodes. The interdigital split electrodes forming the sensitive area significantly enhance the sensitivity to changes in relative permittivity, dielectric losses and electrical conductivity of the eluate In addition, the split-ring resonator is a small, inexpensive and easy-to-use detector that uses several dielectric parameters simultaneously for the measurement. Furthermore, the split-ring resonator measures these parameters at a significantly lower frequency than optical detectors and therefore measures different changes in frequency-dependent permittivity. For demonstrating feasibility of a split-ring resonator as a detector for high-performance liquid chromatography and ion chromatography, various anion and cation standards, basic and acidic amino acids, sugars, as well as sugar alcohols were separated and detected. A conductivity detector for ion chromatography and a refractive index detector for high-performance liquid chromatography were used as reference detectors.